Detection of mecA gene of methicillin resistant Staphylococcus aureus by PCR assay from raw milk - GANAI, AAFREEN WAHID; KOTWAL, S K; WANI, NAJIMAANA; MALIK, M A; JEELANI, RIZWAN; KOUR, SUMEET; ZARGAR, RIZWANA (The Indian Journal of Animal Sciences, 2016)
The occurrence of Staphylococcus aureus and MRSA in foods of animal origin, pose a serious threat to the well- being of humans due to innumerable clinical implications. There is a potential risk of transmission of S. aureus and methicillin-resistant Staphylococcus aureus transmission to humans through raw milk if consumed without maintaining adequate hygienic standards. This study was conducted to assess the prevalence of S. aureus and MRSA from raw milk samples vis-à-vis their phenotypic and genotypic characterization for antimicrobial resistance pattern and presence of mecA gene in raw milk samples of cattle, buffalo and goat in the Jammu city of Jammu and Kashmir. Samples (60) were subjected to California mastitis test to check for their mastitic status. The organisms were cultured and identified on the basis of their cultural, morphological, staining and various biochemical characteristics. The amplification of the mecA gene generated a product with a band size of 533bp upon agarose gel electrophoresis. The S. aureus prevalence was 60, 52 and 60% in raw milk of cattle, buffalo and goat, respectively. Out of 34 S. aureus isolates, 44.1% were MRSA positive.